Recent advances in mitochondrial diseases: From molecular insights to therapeutic perspectives - Ahmad M. Aldossary; Essam A. Tawfik; Mohammed N. Alomary; Samar A. Alsudir; Ahmed J. Alfahad; Abdullah A. Alshehri; Fahad A. Almughem; Rean Y. Mohammed; Mai M. Alzaydi (Elsevier, 2022)
Mitochondria are double-membraned cytoplasmic organelles that are responsible for the production of energy in eukaryotic cells. The process is completed through oxidative phosphorylation (OXPHOS) by the respiratory chain (RC) in mitochondria. Thousands of mitochondria may be present in each cell, depending on the function of that cell. Primary mitochondria disorder (PMD) is a clinically heterogeneous disease associated with germline mutations in mitochondrial DNA (mtDNA) and/or nuclear DNA (nDNA) genes, and impairs mitochondrial structure and function. Mitochondrial dysfunction can be detected in early childhood and may be severe, progressive and often multi-systemic, involving a wide range of organs. Understanding epigenetic factors and pathways mutations can help pave the way for developing an effective cure. However, the lack of information about the disease (including age of onset, symptoms, clinical phenotype, morbidity and mortality), the limits of current preclinical models and the wide range of phenotypic presentations hamper the development of effective medicines. Although new therapeutic approaches have been introduced with encouraging preclinical and clinical outcomes, there is no definitive cure for PMD. This review highlights recent advances, particularly in children, in terms of etiology, pathophysiology, clinical diagnosis, molecular pathways and epigenetic alterations. Current therapeutic approaches, future advances and proposed new therapeutic plans will also be discussed.